Pemanfaatan Gawai sebagai Sumber Literasi Membaca Peserta didik di Sekolah Menengah Atas : Utilization of Devices as a Source of Reading Literacy for Students in Senior High School - ferdiawan, ferdiawan; Maulidi, Ahmad; Muh. Soktumansyah, Andi; Suharto, Suharto (Department of Social Studies Education, Faculty of Tarbiyah and Teacher Training, Datokarama State Islamic University of Palu, Central Sulawesi, Indonesia., 2024)
In Indonesia, the use of devices as learning aids is increasingly popular. With easier access to devices such as smartphones and tablets, students have the opportunity to broaden their horizons through digital literacy resources. E-book applications, online articles, and online education platforms have become part of the teaching and learning process in many schools. This research employs a qualitative descriptive research approach. The data collected were obtained using interview and questionnaire techniques, making the data sources derived from interviews and questionnaires. The qualitative data analysis technique involves directly analyzing the utilization of devices in enhancing the culture of reading literacy. Based on the observations above, gadgets are fundamentally useful for entertainment and social media, but on the other hand, they can also serve as a means to cultivate reading literacy. A total of 59.8% of students agree that gadgets can be utilized to enhance reading literacy, 35.9% state that they may provide benefits in fostering reading literacy, and 9.8% admit they do not benefit from increasing reading literacy at Al Azhar Mandiri Palu High School. Based on the utilization of gadgets as a literacy source at Al Azhar Mandiri Palu High School, students have experienced a significant increase in reading literacy. However, to maintain positive reading habits, concrete steps are needed, such as providing space for students to discover reading content they are interested in, expanding access to various types of reading materials at school, and continuously evaluating reading interest.